Cinema e doença: representações da enfermidade através da série Alien - Oliveira, Jefferson Luis Ribas de (2010)
The problematic of this paper is to discuss how the representation of illness can be visualized in movies of the series of Scientific Fiction Series Alien, one of the most popular cinematic saga of all times, and in what way the illness ideia is there presented. The sources used on this research are the four movies of this North American serie: Alien (Ridley Scott, 1979), Aliens (James Cameron, 1986), Alien 3 (David Fincher, 1992) and Alien: Ressurrection (Jean-Pierre Jeunet, 1997). The central question of this term paper is to analyze how, through of the representation of the alien , the ideia of the illness is present in movies of this cinematic saga. During this history, countless illness were in a discursive way receiving dark metaphors. Ideas such as pollution, plague, scourge, Wrath, the evil that comes from outside, grounding were a constant in a description of a stigmatize kind of illness, such as Leprosy and Aids. This paper has an aim to interpret how these metaphors about the illness appeared in these movies, which are showed with monstrosity, no nature an escape of the established knowledge. Through film narrative analyses, we showed how the alien being, protagonist of the saga is exactly presented like these allegories about the illness idea. Equally we also looked for questioning how the body idea is treated in movies, articulating to it the thematic of the human genetic to a new totalitarism of the private initiative that is overlapped in relation to the State power. Although the Hollywood movie can be considered one of the most sophisticated of way of what was stipulated to call cultural industry, we proposed with this research demonstrate that these cinematic productions has its value as historic documents, which the deep analyse can reveal riveting questions about countless thematics, what helps to show how much the cinema is an extremely rich language, since its narratives are part of a component of the social imaginary, and it is lived when the film period that the film piece are performed, certainly it becomes fertile fields in order to make possible to visualize some fears which the current tine demonstrates.